2018
DOI: 10.2147/ndt.s155987
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an Arabic computerized battery for cognitive rehabilitation of children with specific learning disabilities

Abstract: PurposeThe aim of this study was to design an Arabic computerized battery of cognitive skills for training children with specific learning disabilities (SLD).Subjects and methodsNineteen students from fourth grade primary schools in Assiut, Egypt, who were previously diagnosed with SLD, agreed to participate in the rehabilitation program. The study passed through four stages: first stage, detailed analysis of the cognitive profile of students with SLD (n=19), using a previously constructed diagnostic cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The first assumption: cognitive family-based rehabilitation (sustained attention, working memory, and inhibition) has effects on the executive functions of male children between 10 and 14 years old. Given the multi-variable covariance, it seems that there is a significant difference between the two groups that is consistent with some studies (5)(6)(7)(8), but it is non-consistent with previous studies [15][16][17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The first assumption: cognitive family-based rehabilitation (sustained attention, working memory, and inhibition) has effects on the executive functions of male children between 10 and 14 years old. Given the multi-variable covariance, it seems that there is a significant difference between the two groups that is consistent with some studies (5)(6)(7)(8), but it is non-consistent with previous studies [15][16][17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 51%
“…Children with ID have difficulty in controlling their impulses, organizing, prioritizing, and coordinating the information they receive because of weakness in underlying mechanisms [14]. Previous studies evaluated the effects of inhibition training in ID and reported that such intervention has significant effects [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%